Rituximab in the Treatment of Jo1 Antibody-associated Antisynthetase Syndrome: Anti-Ro52 Positivity as a Marker for Severity and Treatment Response - Bauhammer, Jutta; Blank, Norbert; Max, Regina; Lorenz, Hanns-Martin; Wagner, Ulrich; Krause, Dietmar; Fiehn, Christoph (Journal of rheumatology, 2016)
Rituximab (RTX) has been used successfully for the treatment of severe Jo1 antibody-associated antisynthetase syndrome. The aim of this retrospective study was to evaluate the effect of RTX in severe Jo1 antisynthetase syndrome and determine predictive factors for response. There were 61 patients with Jo1 antisynthetase syndrome identified; 18 of these received RTX. One patient was lost to followup. The remaining 17 patients and 30 out of 43 patients who were treated with conventional immunosuppressive (IS) drugs were followed for a mean of 35 months and 84 months, respectively. Polymyositis/dermatomyositis (95%) and interstitial lung disease (ILD; 66%) were the dominant clinical manifestations. Detection of anti-Ro52 antibodies (43%) was significantly associated with acute-onset ILD (p = 0.016) with O2 dependency, and patients with high concentrations of anti-Ro52 (20%) had the highest risk (p = 0.0005). Sixteen out of 18 patients (89%) showed a fast and marked response to RTX. Among those patients who were highly positive for anti-Ro52, response to RTX was seen in 7 out of 7 cases (100%), but no response to cyclophosphamide (n = 4), cyclosporine A (n = 3), azathioprine (n = 9), methotrexate (n = 5), or leflunomide (n = 2) was observed. One patient treated with RTX died of pneumonia. RTX is effective in the treatment of severe forms of Jo1 antisynthetase syndrome. In our retrospective study, the presence of high anti-Ro52 antibody concentrations predicts severe acute-onset ILD and nonresponse to IS drugs. In contrast to conventional IS, RTX is equally effective in patients with Jo1 antisynthetase syndrome, independent of their anti-Ro52 antibody status.